Receptor tyrosine kinase inhibition by regorafenib/sorafenib inhibits growth and invasion of meningioma cells. (March 2017) - Tuchen, Marcus; Wilisch-Neumann, Annette; Daniel, Evelyn A.; Baldauf, Lisa; Pachow, Doreen; Scholz, Johannes; Angenstein, Frank; Stork, Oliver; Kirches, Elmar; Mawrin, Christian
Abstract: Systemic chemotherapeutic treatment for unresectable and/or aggressive meningiomas is still unsatisfying. PDGF receptor (PDGFR)-mediated activation of mitogenic signalling has been shown to be active in meningiomas. Therefore, we evaluate in vitro and in vivo the effects of inhibiting PDGFR using the clinically well-characterised tyrosine kinase inhibitors sorafenib or regorafenib in meningioma models. IOMM-Lee meningioma cells were used to assess cytotoxic effects, inhibition of proliferation, induction of apoptosis, as well as inhibition of migration and motility by sorafenib and regorafenib. Using an orthotopic mouse xenograft model, growth inhibition as monitored by magnetic resonance imaging, and overall survival of sorafenib- or regorafenib-treated mice compared with control animals was determined. Treatment of malignant IOMM-Lee cells resulted in significantly reduced cell survival and induction of apoptosis following regorafenib and sorafenib treatment. Western blots showed that both drugs target phosphorylation of p44/42 ERK via downregulation of the PDGFR. Both drugs additionally showed significant inhibition of cell motility and invasion. In vivo, mice with orthotopic meningioma xenografts showed a reduced volume (n.s.) of signal enhancement in MRI (mainly tumour) following sorafenib and regorafenib treatment. This was translated in a significantly increased overall survival time (p ≤ 0.05) for regorafenib-treated mice. Analyses of in vivo -grown tumours demonstrated again reduced PDGFR expression and expression/phosphorylation of p44/42. Sorafenib and regorafenib show antitumour activity in vitro and in vivo by targeting PDGFR and p44/42 ERK signalling. Highlights: Sorafenib/regorafenib reduces meningioma cell survival by inhibiting PDGF-R. Sorafenib/regorafenib inhibits meningioma cell motility and invasion in vitro . Mice treated with regorafenib/sorafenib show reduced PDGF-R levels in orthotopic tumours. Mice treated with regorafenib have increased survival time following orthotopic meningioma xenograft growth.